MECHANISMS FOR PROMOTING SUSTAINABLE DEVELOPMENT: LOCATION AND ROLE OF SOCIAL SPHERE - Kutsenko, V. I. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The article is devoted to topical issues of formation of sustainable development in Ukraine. In this regard, the essence of sustainable development is revealed in the context of the place and role of the social sphere as its the leading factor. The structure and main components of sustainable development are revealed. The role in the process of sustainable development of the social sphere is noted, in particular, its components such as education, health care, culture, organized recreation. The analysis of relevant socio-economic indicators was performed. Particular attention is paid to identifying the problems of development of these components of the social sphere in the context of globalization and European integration. We prove that in these conditions serious changes occur with the main productive force, in particular, the growth of the educational and cultural level of workers of modern production. We emphasize the growth of the specific weight of mental activity. The strategy of managing sustainable development processes is disclosed taking into account the factors influencing these processes. The attention is focused on the fact that the development of the social sphere contributes to the acceleration of the development of productive forces, the convergence of material and cultural conditions of life, predetermines significant changes in the system of social relations, which allows for sustainable development. Considerable attention is paid to the formation of mechanisms to ensure the growth of the educational and intellectual potential of the country and the promotion of human health - the main productive force of society, as well as mechanisms that ensure the efficient use of resources, which contributes to the sustainable development of both the economy in general and the social sphere in particular. Thus, it is important not only to ensure the growth of the social sphere, but also its effective use.